2022
DOI: 10.1088/1361-6668/ac8b3e
|View full text |Cite
|
Sign up to set email alerts
|

Reversible critical current performance of FeSe0.5Te0.5 coated conductor tapes under uniaxial tensile strain

Abstract: FeSe0.5Te0.5 coated conductor as a kind of 11-type iron-based superconductor is currently attracting much attention. Recently, the bare FeSe0.5Te0.5 coated conductor tapes were developed by Shanghai Jiao Tong university and verified their superconductivity. For the future application, the FeSe0.5Te0.5 tapes should be subjected to the high electromagnetic forces and stress-strain. In this study, the authors encapsulated the bare FeSe0.5Te0.5 coated conductor tapes with copper layers to enhance the mechanical pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The silver layer easily partially separates from the superconducting layer, damaging the superconductivity of the tape. In order to strengthen the mechanical properties of the FeSe 0.5 Te 0.5 tape, the FeSe 0.5 Te 0.5 tape was encapsulated at the Institute of Plasma Physics, Chinese Academy of Sciences (ASIPP) [21]. In this study, the strengthened FeSe 0.5 Te 0.5 encapsulated tape is 10.5 mm in width and 0.15 mm in thickness.…”
Section: Fese 05 Te 05 Tape Encapsulationmentioning
confidence: 99%
“…The silver layer easily partially separates from the superconducting layer, damaging the superconductivity of the tape. In order to strengthen the mechanical properties of the FeSe 0.5 Te 0.5 tape, the FeSe 0.5 Te 0.5 tape was encapsulated at the Institute of Plasma Physics, Chinese Academy of Sciences (ASIPP) [21]. In this study, the strengthened FeSe 0.5 Te 0.5 encapsulated tape is 10.5 mm in width and 0.15 mm in thickness.…”
Section: Fese 05 Te 05 Tape Encapsulationmentioning
confidence: 99%
“…Meanwhile, the J c is higher than 1 MA/cm 2 in self-field and still 0.1 MA/cm 2 in fields as high as 30 T, demonstrating their enormous potential for high-field applications. A recent research study by Liu et al has shown that the irreversible tensile strain limit of FST CCs is 0.29%, making them quite attractive for magnet applications.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the J c is higher than 1 MA/cm 2 in self-field and still 0.1 MA/cm 2 in fields as high as 30 T, 16 demonstrating their enormous potential for high-field applications. A recent research study by Liu et al has shown that the irreversible tensile strain limit of FST CCs is 0.29%, 25 making them quite attractive for magnet applications. Currently, most studies on IBS CCs have been conducted with a superconducting layer below a few hundred nanometers, 26 yielding a low critical current I c or engineering critical current density J e , which are more important practical parameters for applications such as magnets, despite a high J c .…”
Section: ■ Introductionmentioning
confidence: 99%
“…The iron chalcogenide FeSe1−𝑥Te𝑥 superconductor [1] is regarded as a candidate for studying topological superconductivity [2][3][4][5] and is also promising in practical applications. [6][7][8] It is essential to synthesize high-quality FeSe1−𝑥Te𝑥 single crystals with bulk superconductivity for investigating the intrinsic physical properties. [9][10][11][12][13][14][15][16] The as-grown Fe 1+𝛿 Se1−𝑥Te𝑥 single crystals with the self-flux method inherently contains excess Fe atoms (𝛿 in quantity) for Te substitution 𝑥 > 0.5, which occupy the interstitial sites of the Fe(Se,Te) layers.…”
mentioning
confidence: 99%